1995
DOI: 10.1007/bf00119146
|View full text |Cite
|
Sign up to set email alerts
|

Towards nonpeptide agonists: Design of ?true? peptidomimetics

Abstract: This paper outlines the basic strategy to design 'true' peptidomimetics, i.e., nonpeptide compounds that bind to the same receptor site as the parent peptide. Design of highly selective and potent agonist analogs of 8-opioid peptides based on development of the 3D model for the 8-opioid pharmacophore is described. The design employed molecular modeling in combination with synthesis, biological testing, NMR spectroscopy and X-ray studies. The designed compounds were able to bind to 8-opioid receptors with affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Additionally, an amino group may be introduced on the cyclohexane scaffold to overlap the corresponding amino group of the peptide ligand as shown in Figure . It also has been shown that the increased hydrophobicity of the tyrosine derivatives and the β-dimethyl groups in both d -Pen residues may contribute to the enhanced selectivity and binding affinity of the peptide ligand. ,, Thus, we introduced additional substituents R, of variable size and hydrophobicity, attached to the benzyl carbon of the phenol side-chain group as shown in Figure , to test how this would affect the selectivity and binding affinity of these designed peptidomimetics. To facilitate the synthetic process, we used 1,4-piperazine as a 6-membered ring scaffold for the first generation of peptidomimetics.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, an amino group may be introduced on the cyclohexane scaffold to overlap the corresponding amino group of the peptide ligand as shown in Figure . It also has been shown that the increased hydrophobicity of the tyrosine derivatives and the β-dimethyl groups in both d -Pen residues may contribute to the enhanced selectivity and binding affinity of the peptide ligand. ,, Thus, we introduced additional substituents R, of variable size and hydrophobicity, attached to the benzyl carbon of the phenol side-chain group as shown in Figure , to test how this would affect the selectivity and binding affinity of these designed peptidomimetics. To facilitate the synthetic process, we used 1,4-piperazine as a 6-membered ring scaffold for the first generation of peptidomimetics.…”
Section: Resultsmentioning
confidence: 99%
“…The 3D structures of the rigid δ‐opioids SIOM, OMI, and NTI have been used to corroborate or select potential biologically active conformations of constrained peptide δ‐opioid agonists and antagonists 24, 26, 46. In particular, a proposed bioactive conformation of the cyclic tetrapeptide agonist JOM‐1347 showed good overlap with the tyramine moieties of SIOM and OMI, and a reasonable match of the Phe 3 ring with the indanyl moiety of SIOM 46.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to an unconstrained segmental motion of the exocyclic N‐terminal moiety, and the significant mobility of the Phe 4 side chain, a number of sterically consistent 3D configurations of pharmacophore groups of each peptide had to be taken into account, and results of pharmacophore matching were highly dependent on the set of compounds considered and the conformational search procedure used in a particular study. Although the model proposed by Nikiforovich et al10 was used to predict several active constrained δ‐opioid peptides,26 no consensus on a putative biologically active conformation of DPDPE was reached in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations